The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/ijerph18116044
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Test of Measurement Invariance of the Adapted Health Consciousness Scale (HCS-G)

Abstract: The objective of this study was the translation and validation of a health consciousness scale in order to provide an economically and empirically confirmed measurement of health consciousness, which is associated with health-related behavior. We evaluated this translation on the basis of psychometric testing in a German convenience sample. A cross-sectional online survey (n = 470) was carried out using a translated version of the health consciousness scale, oriented on the basis of international guidelines. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Higher values imply more health consciousness. The psychometric properties of the scale have been verified in studies, which also have presented a correlation between HCS scores and multiple health behaviors and practices ( Gould, 1988 , 1990 ; Marsall et al, 2021 ). Additional studies have validated the psychometric properties of the scale among racial/ethnic minoritized samples ( Espinosa & Kadić-Maglajlić, 2018 , 2019 ).…”
Section: Methodsmentioning
confidence: 88%
“…Higher values imply more health consciousness. The psychometric properties of the scale have been verified in studies, which also have presented a correlation between HCS scores and multiple health behaviors and practices ( Gould, 1988 , 1990 ; Marsall et al, 2021 ). Additional studies have validated the psychometric properties of the scale among racial/ethnic minoritized samples ( Espinosa & Kadić-Maglajlić, 2018 , 2019 ).…”
Section: Methodsmentioning
confidence: 88%
“…In addition, consumers are very concerned about the certification and raw components of each product they use, showing a fairly high concern for their own health). Research conducted by Xu et al, 2020b;Kusumaningsih et al, 2019;Nguyen et al, 2019;and Marsall et al, 2021 showed that health consciousness has a significant effect on purchase intention of green products. Hypothesis 3: Health consciousness affects the purchase intention of green cosmetics.…”
Section: Introductionmentioning
confidence: 99%